Pachinko [compact disc, unabridged] - Lee, Min Jin (Hachette Audio, 2017)
In early 1900s Korea, prized daughter Sunja finds herself pregnant and alone, bringing shame on her family until a young tubercular minister offers to marry her and move with her to Japan, in the saga of one family bound together as their faith and identity are called into question.